What should patients learn? Co-designing patient education to improve medication safety, professional-patient communication, and partnership - Hendrix, Z. Noah; Jallow, Fatoumata; Fulda, Kimberly G.; Young, Richard A.; Espinoza, Anna M.; Gurses, Ayse P.; White, Annesha; Xiao, Yan (Frontiers in Medicine, 2025)
IntroductionAdverse drug events are a major focus of patient safety research, but work is often limited to healthcare professionals’ actions and inpatient populations. The patient work system provides a framework to understand the work done by patients and other nonprofessionals. The authors aimed to improve medication safety through the development of short educational videos designed to facilitate professional-patient partnership and shared decision-making by addressing the knowledge gaps and information asymmetry that serve as barriers to productive primary care encounters.MethodsThe authors first performed a narrative review to identify knowledge gaps and the most important medication management principles for patients to learn. Next, the authors conducted participatory design workshops with professionals and patients to develop a list of topics for the educational videos. Lastly, the authors surveyed professionals (N = 44) and patients (N = 100) to measure interest in the proposed video topics.ResultsThe narrative review identified two themes: (1) knowledge-based barriers and hazards, and (2) opportunities for education-based solutions. The design workshops resulted in a proposed list of 12 educational videos divided into four modules: ownership, partnership, system, and learning. Two-factor ANOVA testing of the survey results showed that there was a significant difference in interest with professionals being more interested than patients (p < 0.001). Post-hoc testing revealed that patients were significantly more interested in watching videos from the partnership module than from the system module (p < 0.05).DiscussionInformation asymmetry provides a framework to understand why some patients defer decision-making to professionals while also showing the greatest interest in the partnership module. It also highlights why it is important for professionals to tell patients about their desire for patient ownership of care—engaged patients provide better information to professionals, who might otherwise work with incomplete records. To improve medication safety, patient education efforts should include a focus on how patients can partner with HCPs and be mindful of the work system barriers that patients will encounter while performing the educational work. Successful efforts stand to improve patient outcomes by reducing information asymmetry and enabling shared decision-making.